1987
DOI: 10.1002/ar.1092190305
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic and autoradiographic characterization of hindlimb muscle regeneration in the mdx mouse

Abstract: The pattern of postnatal growth and development of skeletal muscle in mdx mice was studied by light and transmission electron microscopy and by autoradiography and was compared with that in their normal age-matched controls at 4 and 32 weeks of age. The muscle weights of both the extensor digitorum longus (EDL) and soleus muscles of mdx mice were significantly greater than those in control mice at both ages. Body weights of male and female mdx mice were also increased over controls up to 12 weeks of age. At 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 43 publications
7
78
2
Order By: Relevance
“…First, mdx mice might have greater regenerative capacity in their skeletal muscle compared with humans with muscular dystrophy. [17][18][19][20][21][22] Second, mdx mice can show up-regulation of utrophin that may partially compensate for the lack of dystrophin, thus reducing pathological manifestations of disease somewhat. In contrast, humans with DMD show no significant utrophin up-regulation and are characterized by progressive muscle degeneration with satellite cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…First, mdx mice might have greater regenerative capacity in their skeletal muscle compared with humans with muscular dystrophy. [17][18][19][20][21][22] Second, mdx mice can show up-regulation of utrophin that may partially compensate for the lack of dystrophin, thus reducing pathological manifestations of disease somewhat. In contrast, humans with DMD show no significant utrophin up-regulation and are characterized by progressive muscle degeneration with satellite cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…This regeneration results in the formation of additional muscle fibers, which leads to a significant level of muscle hypertrophy. Hypertrophy in rndx muscle is characterized by a 25% increase in the number of fibers, a four-fold increase in the distribution of the fiber calibers, centrally located nuclei within 70%-80% of all fibers, and a 1 .-/-fold increase in muscle mass (Anderson et al 1987;Carnwath and Shotton 1987;Coulton et al 1988; e.g., see Fig. 2, below; Table 1).…”
Section: Mice Lacking Myod and Dystrophin Exhibit Increased Myopathymentioning
confidence: 99%
“…These data suggest that MyoD has a role in the postnatal growth of skeletal muscle. The rndx phenotype is characterized by an -1.7-fold increase in the mass of individual skeletal muscles compared with wild-type mice (Anderson et al 1987;Carnwath and Shotton 1987;Coulton et al 1988; e.g., see Fig. 2 and Table 1).…”
Section: Mice Lacking Myod and Dystrophin Exhibit Increased Myopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we generated a novel Lmo7-null (lmo7 Ϫ/Ϫ ) mouse with deletion of all three isoforms. Using these mice, we examined skeletal and cardiac muscle physiology, as well as the role of Lmo7 in a model of muscular dystrophy and regeneration using the dystrophindeficient mdx mouse model (1,6). Despite loss of all Lmo7 isoforms, our results demonstrated that lmo7 Ϫ/Ϫ mice had no abnormalities in skeletal muscle morphology, physiological function, or regeneration.…”
mentioning
confidence: 94%